A case study of sulphur dioxide identification in three different volcanic eruptions, using Infrared satellite observations (IASI). (July 2016) - Athanassiadou, Maria; Francis, Peter N.; Saunders, Roger W.; Atkinson, Nigel C.; Hort, Matthew C.; Havemann, Stephan; Thelen, Jean‐Claude; Bush, Mike
ABSTRACT: Volcanic eruptions are natural hazards with dire consequences to life and economy. As most volcanoes are in remote areas, satellites play a vital role in providing observations and input to models used for forecasting volcanic plume evolution. Radiances from the Infrared Atmospheric Sounding Interferometer (IASI) on board the MetOp polar orbiting meteorological satellites were used to detect sulphur dioxide (SO2 ) from three volcanic eruptions in 2014, in different meteorological situations. Two of these eruption cases, Mount Sinabung in January and Kelut in February, are in the tropics, whereas the case in October from Bárðarbunga, is at a higher latitude. The SO2 plumes from these volcanic eruptions were identified easily and tracked using established methods from the literature, that are based on the principle that areas of increased SO2 from the volcano produce a reduction in the spectrum of the observed radiances (in the relevant absorption bands of IASI), whereas areas outside the volcanic plume do not. An estimate of the plume height was obtained in the first two cases by examination of the winds from an NWP model at different heights, and in the third, where the meteorological pattern is more complicated, by using trajectories from a Lagrangian model and matching their position with satellite observations of the plume at different times. The importance of meteorology in the detection and evolution of volcanic plumes, especially at low levels, is especially well demonstrated by the Bárðarbunga eruption. Estimates of the plume concentrations were obtained from explicit line‐by‐line calculations.